Encuesta sobre derechos fundamentales - -, - (Teoría y Realidad Constitucional, 2007)
t is approached in this survey the constitutional treatment of the fundamental rights. This way, for example, the systematic of the Title I of the Constitution, the nature of the principles rectors or the different approaches of the limitation of rights.